Fostering creativity to design biodiversity-based cropping systems that consider the long term: a participatory framework - Delbaere, Arnaud; Carof, Matthieu; Godinot, Olivier; Le Cadre, Edith (Frontiers in Agronomy, 2025)
Biodiversity-based cropping systems can address sustainability challenges currently faced by agriculture and provide long-term benefits such as climate-change mitigation and other ecosystem services. However, short-term socio-economic and technical challenges encourage adherence to established paradigms halting the implementation of such systems in farms. In response, we developed a new framework that combines a fictional narrative and information about plant functional ecology to facilitate the co-design of biodiversity-based cropping systems. To demonstrate the interest of this framework, a participatory workshop was conducted in which participants selected crop species based on functional traits and collaboratively designed crop rotations. Both quantitative evaluation of co-designed crop rotations by ecological indices and qualitative evaluation by the satisfaction assessment of the framework by participants were performed. Our approach showed that the two co-designed crop rotations had higher biodiversity than the two reference rotations used in the study: the dominant (maize (Zea mays) – wheat (Triticum aestivum) – catch crop (white mustard (Sinapis alba)) and a highly diversified rotation designed to reduce the use of pesticides (10 taxonomic species). Using a fictional narrative as a trigger event (being stranded on a deserted island) was instrumental in expanding possibilities and stimulating creativity among the participants, which helped them design diverse crop rotations that contained taxonomical and functional diversity. Our framework demonstrated a potential to co-design biodiversity-based cropping systems by abstraction.